Comparison of experiences of nursing staff and patients before and after move to 100% single-bed room hospital in Australia: mixed methods - Lynette Cusack; Rebecca Munt; Naomi Verdonk; Tim Schultz; Jill Maben (BMC, 2023)
Abstract Background There is sufficient and consistent international evidence of issues reported by nurses working in single-bed room environments, requiring a design that is not only comfortable for patients but meets nurses working needs. This paper presents a comparison of nursing staff and patients experience prior to a move to 100% single-bed room hospital in 2016 (Stage 1) and actual experiences after the move in 2021 (Stage 2) in South Australia. Method Mixed method case study design. Survey sample of forty-two nursing staff; twelve patient interviews of their experiences of current environment and; thirteen nursing staff interviews of their experiences delivering nursing care in 100% single bed-room environment. Results Nurses and patients highlighted single-bed rooms contributed to patients' privacy, confidentiality, dignity and comfort. As anticipated in Stage 1, nurses in Stage 2 reported lack of patient and staff visibility. This impacted workload, workflow and concern for patient safety. Conclusion Patient and nursing staff experiences are interdependent, and implications of single-bed room accommodation are complicated. Future impacts on the health system will continue to affect hospital design, which must consider nurses working needs and patient safety and comfort.